2012
DOI: 10.1108/08858621211236043
|View full text |Cite
|
Sign up to set email alerts
|

Customer intimacy

Abstract: PurposeThe term customer intimacy has been used both in academia and business, albeit lacking clear definition and empirical validation. The authors in this paper aim to develop a measure of customer intimacy in business‐to‐business contexts and to assess its reliability and validity, as well as its relevance, within a nomological relationship marketing network.Design/methodology/approachA multi‐method (qualitative/exploratory and quantitative/confirmatory structural modelling), multi‐staged (test, re‐test) re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(19 citation statements)
references
References 77 publications
0
14
0
1
Order By: Relevance
“…For instance, studies showed good and significant effect on organisational performance and customer intimacy like (Wang & Lo, 2003;Yim, Tse, & Chan, 2008;Tuominen, Rajala, & Möller, 2001;Habryn, Blau, Satzger, & Kölmel, 2010;Brock & Zhou, 2012) in developed countries; and in developing countries like (Wang & Lo, 2003;Yim, Tse, & Chan, 2008). Similarly, the relationship was observed in competitive advantage aspect.For example; in the U.S. (Yim, Tse, & Chan, 2008;Bügel, Buunk, & Verhoef, 2010); Sweden , the U.K. Anderson, Healey, & Locke, 2005;Gooderham, 2016) and India (Indian Institute of Technology Bombay, 2016;Kamath, 2016).…”
Section: Findings and Discussionmentioning
confidence: 72%
See 4 more Smart Citations
“…For instance, studies showed good and significant effect on organisational performance and customer intimacy like (Wang & Lo, 2003;Yim, Tse, & Chan, 2008;Tuominen, Rajala, & Möller, 2001;Habryn, Blau, Satzger, & Kölmel, 2010;Brock & Zhou, 2012) in developed countries; and in developing countries like (Wang & Lo, 2003;Yim, Tse, & Chan, 2008). Similarly, the relationship was observed in competitive advantage aspect.For example; in the U.S. (Yim, Tse, & Chan, 2008;Bügel, Buunk, & Verhoef, 2010); Sweden , the U.K. Anderson, Healey, & Locke, 2005;Gooderham, 2016) and India (Indian Institute of Technology Bombay, 2016;Kamath, 2016).…”
Section: Findings and Discussionmentioning
confidence: 72%
“…In developed countries, studiessuch as (Wang & Lo, 2003;Yim, Tse, & Chan, 2008;Tuominen, Rajala, & Möller, 2001;Habryn, Blau, Satzger, & Kölmel, 2010;Habryn, Blau, Satzger, & Kölmel, 2010;Brock & Zhou, 2012) have identified the positive relationship between customer intimacy and organisational performance in different countries. However, these studies have failed to provide in-depth information on a specific strategy that the companies have adopted to interact with customers.…”
Section: Customer Intimacy and Organisational Performancementioning
confidence: 99%
See 3 more Smart Citations